Analisis Pengaruh Pendalaman Keuangan terhadap Pertumbuhan Ekonomi di Indonesia: Supply-Leading Hypothesis - Sutarji, Theana Dominica; Hayati, Banatul (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2024)
The supply-leading hypothesis states that financial deepening has a positive effect on economic growth. This paper examines the effect of financial deepening on economic growth in Indonesia for the period 1980–2019. This study uses the Error Correction Model (ECM) approach to analyze financial deepening and economic growth in both the short and long run. The results show that the broad money-to-GDP ratio (M2/GDP), the financial institutions depth index, and the financial market depth index have a positive and significant effect on economic growth in the long run, while only the broad money-to-GDP ratio (M2/GDP) has a positive and significant effect on economic growth in the short run. This implies that financial deepening can stimulate economic growth in Indonesia. Therefore, this study supports the supply-leading hypothesis.